St. Vincent and the Grenadines : foreign policy 1979-1995 : (notes on protocol) - Browne, Brendon ([s.n.] [S.l.], 1995)
Focuses on the relations of St. Vincent and the Grenadines with several countries, and provides some tips on Protocol.